Recent achievements in CAR-T cell immunotherapy for glioblastoma treatment - S. V. Timofeeva (SPb RAACI, 2021)
Glioblastoma remains the most common and aggressive primary brain tumor today. Because of the neuroanatomical location of glioblastoma, conventional chemotherapy and radiation therapy have limited efficacy in patients with these tumors. Over the past decade, antitumor immunotherapy has become widespread among modern therapeutic approaches. The importance of immunotherapeutic methods lies in their ability to increase the effectiveness of cancer treatment and prevent relapses by enhancing the systemic and local immune response against tumor cells.One of the most promising directions in modern immunotherapy is CAR-T therapy, or adoptive cell therapy using genetically modified T-lymphocytes. The functional advantage of CAR-T therapy is its ability to genetically modify lymphocytes, leading to their activation in vitro.This review examines the key principles of CAR-T therapy and analyzes the published results of clinical trials for the treatment of glioblastoma using several modifications of CAR-T cells.